2022
DOI: 10.1177/10711007221112090
|View full text |Cite
|
Sign up to set email alerts
|

The First Tarsometatarsal Joint in Lisfranc Injuries

Abstract: Background: Lisfranc injuries are among the most debilitating injuries to the foot. Characterization of first tarsometatarsal (TMT) joint involvement in Lisfranc injuries is limited. Multiple studies have indicated that this joint is damaged in a variety of Lisfranc injury patterns, but there is sparse information regarding how often and in what form. Methods: A retrospective review was performed of operative Lisfranc fractures from 2010 to 2020 with patients identified by Combined Procedural Terminology codes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The advantage of CT is in the diagnosis of microfractures and translocations. In the study by Wong et al (34), the most common types of injury in first-ray injuries were joint dislocations and microfractures, which further supported the diagnostic utility of CT in first-ray injuries. However, in the second and cuneiform rays, the CT diagnosis of subtle Lisfranc injuries was inferior to MRI.…”
Section: Discussionmentioning
confidence: 75%
“…The advantage of CT is in the diagnosis of microfractures and translocations. In the study by Wong et al (34), the most common types of injury in first-ray injuries were joint dislocations and microfractures, which further supported the diagnostic utility of CT in first-ray injuries. However, in the second and cuneiform rays, the CT diagnosis of subtle Lisfranc injuries was inferior to MRI.…”
Section: Discussionmentioning
confidence: 75%
“…Although not extensively studied in the literature, it may serve as an adjunct in the diagnosis of subtle injuries and/or in confirming accurate reduction intraoperatively. Injury to the first TMTJ, including articular damage, fracture, and/or joint incongruity, may occur in up to 86% of cases and has been overlooked previously 34 . Fractures of the second metatarsal base with no evidence of radiographic instability at the Lisfranc joint are commonly (but incorrectly) interpreted as Lisfranc injuries and are treated conservatively.…”
Section: Investigationsmentioning
confidence: 99%
“…The presence of high- vs low-energy mechanism does not reliably predict injury pattern. We recently reported on midfoot injuries 5 ; review of our cohort revealed that 35% of homolateral dislocations arose from ground-level falls and 33% of B2 (Lisfranc interval diastasis) were attributable to high-energy mechanisms (motor vehicle crash, crush, and fall from height). This method of characterizing midfoot injury is not perfect, but our observation suggests that sorting injuries by description of mechanism can be imprecise.…”
mentioning
confidence: 98%